LEGAL ASPECTS OF DAMAGES OF PERSONAL DATA OF COVID-19 VACCINATION PARTICIPANTS PERFORMED BY MEDICAL PERSONNEL - Itok Dwi Kurniawan; Kristiyadi Kristiyadi (Sekolah Tinggi Pariwisata Mataram, 2022)
The research by writing this article aims to examine and examine regarding legal protection of personal data of Covid-19 vaccination participants that are misused by medical personnel. During the Covid-19 pandemic, the government carried out an evenly distributed vaccination program throughout Indonesia to prevent and eradicate the spread of Covid-19. However, in the process there were several mistakes made by health workers and the leaking of personal data of vaccine participants on the Peduli Protect.id application. This issue violates the rights of vaccine participants by contacting vaccine participants personally that is not related to the vaccination process. The research method that the author uses in writing this article is the normative legal research method. The results of this study indicate that the dissemination of personal data of Covid-19 vaccination participants is a prohibited act so that a form of legal protection regarding personal data specifically has been regulated in Articles 30-35 of the Electronic Information and Transactions Law so that administrative sanctions and civil lawsuits can be charged to perpetrators. due to misuse of personal data